Oncologic outcomes of microscopic tumor cut through in locally advanced oral squamous cell carcinoma - Guilherme Reimann Agne; Hugo Fontan Kohler; Thiago Celestino Chulam; Clóvis Antônio Lopes Pinto; José Guilherme Vartanian; Luiz Paulo Kowalski (Brazilian Journal of Otorhinolaryngology)
Objective: This study aims to determine the impact of MTCT on local recurrence and disease-specific survival in patients with locally advanced T3-T4 OCSCC and compare it with other clinicopathological variables. Methods: A retrospective database analysis of patients diagnosed with locally advanced T3-T4 OCSCC surgically treated and submitted to intraoperative frozen section guiding the margin status. Survival was analyzed using the Kaplan-Meier estimator followed by the Cox model for multivariate analysis. Results: We analyzed 475 patients who met inclusion criteria: MTCT occurred in 29 patients (6.11%) and local recurrence was observed in 131 patients (27.6%). MTCT had an impact on univariate (HR = 2.205; 95% CI 1.243–3.914; p = 0.007) and multivariate (HR = 1.851; 95% CI 1.285–2.666; p = 0.001) analyses. Similar results were found for disease-specific survival: univariate (HZ = 1.669; 95% CI 1.056–2.635; p = 0.028) and multivariate (HZ = 1.307; 95% CI 0.816–2.092; p = 0.265) analyses. A total of 231 patients (48.6%) had died of cancer by the end of follow-up. The best predictor for compromised frozen sections was tumor depth of invasion. Conclusion: Even after negative final margins, MTCT is an important factor associated with poorer outcome, and treatment intensification should be considered in these patients. Level of evidence: Level III.